Real-time imaging of blood coagulation and angiogenesis during development in a zebrafish model of type I antithrombin deficiency - Yuta Imai; Satoru Ozaki; Taiki Noda; Isao Kobayashi; Kayo Sugitani; Satomi Kasashima; Eriko Morishita; Yuhei Araiso (Scientific Reports)
Abstract Severe type I antithrombin (AT) deficiency is considered to cause embryonic lethality. Although several pathological analyses using mice or zebrafish have been attempted, the previous studies did not unveil the detailed mechanism leading to lethality in the early developmental stage. In order to solve this problem, we established type I AT deficient zebrafish by the CRISPR/Cas9 system into Tg(gata1:dsRed) and Tg(fli1a:GFP) lines, so that we could conduct real-time imaging of thrombosis and angiogenesis using fluorescence stereo zoom microscopy. The established zebrafish AT (zAT) mutants harbored frameshift mutations which resulted to be type I AT deficient, unable to secrete zAT protein into blood. Both heterozygous (zAT+/−) and homozygous (zAT−/−) mutants showed reduced survival rate and diverse thrombosis up to 9 days post fertilization. In addition, blood vessel formation was delayed at 30 hpf in zAT−/−, which was recovered normally by 5 dpf and had little effect on survival. Notably, we analyzed the differences in gene expression profiles under AT-depleted conditions by real-time quantitative PCR, and zAT−/− juvenile zebrafish showed increased PLG gene expression and decreased F2 gene expression. Our in vivo study revealed the effects of AT deficiency on embryos during development from the aspects of coagulation and vascular formation.